Clinical and genetic analysis of melanomas arising in acral sites - Zaremba, Anne; Brinker, Titus Josef (European journal of cancer, 2019)
Study aim - Melanomas arising in acral sites are associated with a poorer prognosis than other melanoma subtypes. The aim of this study was to evaluate clinical-pathological and genetic characteristics as well as therapeutic responses of a larger cohort of patients with melanomas arising in acral sites. - Methods - Clinical data of 134 patients with melanomas arising in acral sites from the Dept. of Dermatology Essen were collected and analysed with regard to clinicopathological characteristics and treatment responses. Genetic analysis with targeted next-generation sequencing was done on 50 samples. - Results - In our cohort, BRAF (30%), NRAS (28%), TERT promoter (26%), NF1 (14%) and KIT (6%) were frequently identified mutations. Comparing tumours situated on palms and soles with melanomas arising on dorsal acral sites, a higher frequency of NRAS (39.1% versus 25%) and NF1 (17.3% versus 0%) and lower frequencies of BRAF (21.7% versus 75%) and TERT promoter (8.6% versus 50%) mutations were observed. MAPK activating mutations were identified in 64% of tumours. Overall survival was longer in patients treated with immune checkpoint inhibitors as first-line treatment than in patients receiving other systemic therapies (i.e. BRAF/MEK inhibitors and chemotherapy). - Conclusion - Our data suggest that the genetics of melanomas arising in acral sites varies by tumour location and may influence biological behaviour.
Gesehen am 06.11.2019